A cartografia do fenômeno urbano e econômico no Paraná: uma leitura com auxílio da semiótica - Ricardo Rodrigues Monteiro (Confins)
This paper presents a narrative of Paraná urban phenomenon from 1872 to 2010 with the help of cartography and Peirce's semiotics. We used IBGE historical data to illustrate eleven times that link major population dynamics: spreading occupation, population growth, density in urban areas and emptying in almost half of the municipalities. It was drawn up maps of six Census 1960-2010 to study the quantitative changes of the population registered as urban and rural. Added to maps with data REGIC 2007, GDB busy in the main sectors of the economy, population change 1991-2010, meso, dismemberment of municipalities, illiteracy, dependency ratio, Gini coefficient, poverty, among others, to aid analysis about the urban phenomenon. Was experienced five funds of maps, including four anamorphosis (Pop. 2010, GDP 2012, antichartogramma and visual equivalence) to present cartographic signs more evolved, or signs representing their territories with greater conformity to reality. The Peirce's semiotics is presented in an introductory way. At all, were elaborated 37 maps that reveal significant aspects to the study of the phenomena associated with the urban phenomenon.